Effets de salons – Quand Zola croise Flaubert - Jean-Michel Pottier (Flaubert: Revue Critique et Génétique)
Flaubert and Zola have common ideas about the social “salons” of their time. They criticize certain aspects of this social life, which is too superficial and useless. However their novels abundantly analyse the functionning of these social groupings. Described as places of observation of the world, the “salons” are also spaces where human relations are played out. They are alsoterritorieslinked to the main characters.